Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26 - 29, 2023, Los Angeles, California - Rathje, Ellen M.; Montoya, Brina; Wayne, Mark H. (GSP (Series) ;, 2023)
This is the third volume of six Geotechnical Special Publications (GSPs) containing papers from the 2023 Geo-Congress. It includes 60 peer-reviewed papers on topics related to geotechnical characterization, including: engineering geology and site characterization; geophysical engineering; rock mechanics; and soil properties and modeling.